T cell receptor variable β gene repertoire in liver and peripheral blood lymphocytes of chronically hepatitis C virus‐infected patients with and without mixed cryoglobulinaemia. (10th April 2013) - Russi, S.; Lauletta, G.; Serviddio, G.; Sansonno, S.; Conteduca, V.; Sansonno, L.; De Re, V.; Sansonno, D.
Summary To characterize the repertoire of T lymphocytes in chronically hepatitis C virus (HCV)‐infected patients with and without mixed cryoglobulinaemia (MC). T cell receptor (TCR) variable (V) β clonalities in portal tracts isolated from liver biopsy sections with a laser capture microdissection technique in 30 HCV‐positive MC patients were studied by size spectratyping. Complementarity‐determining region 3 (CDR3) profiles of liver‐infiltrating lymphocytes (LIL) were also compared with those circulating in the blood. The representative results of TCR Vβ by CDR3 were also obtained from liver tissues and peripheral blood lymphocytes (PBL) of 21 chronically HCV‐infected patients without MC. LIL were highly restricted, with evidence of TCR Vβ clonotypic expansions in 23 of 30 (77%) and in 15 of 21 (71%) MC and non‐MC patients, respectively. The blood compartment contained TCR Vβ expanded clones in 19 (63%) MC and 12 (57%) non‐MC patients. The occurrence of LIL clonalities was detected irrespective of the degree of liver damage or circulating viral load, whereas it correlated positively with higher levels of intrahepatic HCV RNA. These results support the notion that TCR Vβ repertoire is clonally expanded in HCV‐related MC with features comparable to those found in chronically HCV‐infected patients without MC.